Effect of a High-rate Versus a Low-rate Oxytocin Infusion for Maintaining Uterine Contractility During Elective Cesarean Delivery: A Prospective Randomized Clinical Trial. Issue 3 (September 2017) - Duffield, A.; McKenzie, C.; Carvalho, B.; Ramachandran, B.; Yin, V.; El-Sayed, Y.Y.; Riley, E.T.; Butwick, A.J.
Abstract : ( Anesth Analg . 2017;124(3):857–862) Oxytocin is routinely used for prophylaxis against uterine atony after vaginal or cesarean delivery (CD), as it has been shown to decrease the risk of postpartum hemorrhage (PPH). In fact, a low dose delivered during elective CD can initiate adequate uterine tone after placental delivery. However, consensus is lacking on the effective oxytocin infusion rate for achieving this outcome and there exists marked variation in prescribed oxytocin regimens. The authors of the present study thus evaluated the effect of a high-rate (15 U/h) versus low-rate (2.5 U/h) infusion of oxytocin on total estimated blood loss (EBL).